(untitled) (International Journal of Engineering and Computer Science, 2014)
Digital image can be copy from one place to another Place are easily , and our image are distribute from person to person and image easily uploaded on the internet. Images can be appeared widely in the internet and can be copied from the internet. To protect the image applied the watermark. Watermark is method to embed the data into an image. Data must be placed into an actual pixel. Watermarking are two types:1) Visible watermarking and 2) Invisible Watermarking. In proposed system invisible watermarking are used, Because it is more secure as compare to visible watermarking. In this scheme watermark are placed on the gradients vector. This system is more secure as compare to other watermarking scheme . Other scheme are based on coefficient based, hence by using filtering method and compression techniques watermark and image are separated from each other. Proposed system are more secure and in this technique gradient vector are used to embedded the data.